Building a Pedagogical Innovation Ecosystem: The Role of Clinical Supervision in Improving the Quality of Madrasah Aliyah - Istianatul Imamah; Luluk Rosyidatul Umah; Nani Septiana (Universitas Nurul Jadid, 2025)
This study explores how implementing clinical supervision can transform teaching practices and education management in the context of Islamic schools in Indonesia. Effective and sustainable professional development of teachers is crucial to improving the quality of religious and general education. Although clinical supervision is known as a collaborative and reflective approach, its understanding as an instrument of systemic change in a unique Islamic educational environment is still limited. This study uses a qualitative case study method in one of the Aliyah Madrasas, with data collection through in-depth interviews, participatory observation, and document analysis. Key findings show that clinical supervision significantly improves teachers' pedagogical skills, encourages innovation in teaching methods, and fosters a culture of reflective practice. Furthermore, implementing clinical supervision triggers positive changes in school management policies related to teacher professional development and evaluation and strengthens a culture of collaboration between educators. The implications of this study underscore the potential of clinical supervision as a practical and contextual model of teacher development in Islamic educational institutions, providing valuable input for policy formulation and practice for improving continuing education.